PROBLEMATIKA GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK TERPADU : STUDI KASUS SD INPRES 48 INGGRAMUI MANOKWARI - BERTHA DIMARA (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
Teacher Problems in Developing Integrated Thematic RPP at SD Inpres 48 Inggramui West Manokwari District, West Papua Province in 2022. This study aims to analyze the difficulties of teachers in preparing integrated thematic RPP, inhibiting factors and efforts made to overcome teacher difficulties in compiling thematic RPP integrated approach. The approach used is descriptive qualitative single case study design. Sources of data are primary data obtained from school principals, school supervisors and teachers. Secondary data were obtained from observations and checking of documents relevant to the study such as syllabus, lesson plans and teacher journals. Data collection techniques through interviews, observation and documentation. The validity of the data used a credibility of test and validity data, namely triangulation of sources, techniques and reference materials. Data analysis uses data analysis of Milles and Huberman models, namely through data checking, data reduction, data display, and data verification. The results showed that teachers had difficulties in: (1) developing learning indicators, (2) formulating learning objectives, (3) determining learning models and methods, 4) determining learning resources and media, (5) compiling learning steps, (6) create and develop authentic assessments. Inhibiting factors that influence teachers in preparing integrated thematic lesson plans are the lack of; (1) understanding of teachers in the preparation of integrated thematic lesson plans, (2) training in the preparation of integrated thematic lesson plans, (3) availability of time, (4) learning support facilities, (5) motivation and commitment of teachers in developing self-potential, (6) ability to utilize technology. Efforts made by teachers to get out of this difficulty are: (1) teachers actively seek information on various media, do not have to attend training, (2) collaboration between principals and supervisors is intensified, (3) teachers must have high motivation and commitment, ( 4) the teacher's IT skills must be good in order to ease the teacher's work. Some teachers show good progress in several components of the lesson plan, others still need further guidance. ABSTRAKProblematika Guru Dalam Menyusun RPP Tematik Terpadu di SD Inpres 48 Inggramui Distrik Manokwari Barat Provinsi Papua Barat Tahun 2022. Penelitian ini bertujuan untuk menganalisis kesulitan guru dalam menyusun RPP tematik terpadu,faktor penghambat serta upaya yang dilakukan untuk mengatasi kesulitan guru dalam menyusun RPP tematik terpadu.Pendekatan yang digunakan adalah deskriptif kualitatif rancangan studi kasus tunggal. Sumber data adalah data primer yang diperoleh dari Kepala sekolah, pengawas sekolah dan guru. Data sekunder diperoleh dari hasil pengamatan dan pengecekan dokumen yang relevan dengan penelitian seperti silabus, RPP dan jurnal guru. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Keabsahan data menggunakan uji kredibilitas dan validitas data yaitu triangulasi sumber, teknik dan bahan refernsi. Analisis data menggunakan analisis data Model Milles dan Huberman yaitu melalui pengecekan data, reduksi data, display data, verifikasi data. Hasil penelitian menunjukkan bahwa guru kesulitan dalam:(1) mengembangkan indikator pembelajaran,(2) merumuskan tujuan pembelajaran, (3) menentukan model dan metode pembelajaran,(4) menentukan sumber dan media pembelajaran, (5) menyusun langkah-langkah pembelajaran, (6) membuat dan mengembangkan penilaian autentik. Faktor penghambat yang mempengaruhi guru dalam Menyusun RPP tematik terpadu adalah minimnya ; (1) pemahaman guru dalam penyusunan RPP tematik terpadu, (2) pelatihan penyusunan RPP tematik terpadu, (3) ketersediaan waktu, (4) sarana penunjang pembelajaran, (5) motivasi dan komitmen guru dalam menngembangkan potensi diri, (6) kemampuan memanfaatkan teknologi. Upaya yang dilakukan guru agar keluar dari kesulitan ini adalah: (1) guru aktif mencari informasi dari berbagai media, tidak harus mengikuti pelatihan, (2) kolaborasi kepala sekolah dan pengawas lebih diintensifkan, (3) guru harus memiliki motivasi dan komitmen yang tinggi, (4) kemampuan IT guru harus baik agar meringankan pekerjaan guru. Beberapa guru menunjukkan progress yang baik dibeberapa komponen RPP, yang lainnya masih membutuhkan bimbingan lebih lanjut.